O avesso da comunicação: estética e política do ruído na cultura digital - Abraão Filho, Claudio Luiz Cecim (2019)
This doctoral thesis commits to thinking political dimensions of noise from a corpus of images, manifestos and creative practices associated with Glitch art – a form of art that relates to previous aesthetics of noise and is defined by the use of accidents and errors in digital technologies, whether casually found or deliberately induced by means of non-expert bends and modifications in electronic circuits and digital languages. The thesis’ objectives are to underline political dimensions in these images, manifestos and procedures; to think through the aesthetical strategies conformed by practices in which sense and non-sense mutually relate in a complex manner; to apprehend theoretical and conceptual tools in a critical semiotics of noise as a properly communicational problem. Some of the questions that guide the thesis are: which elements constitute the political dimension of Glitch art images? What concept of critical image would correspond to this dimension? What is the role of noise in such a critical project? We work with the hypothesis that Glitch art is political by employing a praxiological critique of certain ways of producing, consuming and thinking images in cyberculture. It is all the more effective in this critique, the more it is capable of promoting expressive ruptures not only at the level of language, but rather in the very materiality of communicational objects which are the condition of possibility for the social circulation of signs and discourses. By bending objects and digital languages, the praxiological critique of cyberculture consubstantiates itself in a materialistic poetics that articulates technical, aesthetic and political dimensions in a renewed understanding on the operation of consumer technologies and its uses. It rescues critical potencies of noise and experimentation like modes of "immanent transgression" to a society obsessed with speed, operational transparency and the cybernetic modulation of behaviors. In this enterprise, the Thesis assembles a constellation of concepts from post-structuralism (Deleuze, Guattari, Derrida), sociodromology and critical epistemology of cyberculture (Trivinho, Virilio), the current critical debate around the image (Didi-Huberman, Flusser , Rancière) and contemporary philosophy (Agamben, Han, Bataille). Specific studies on noise and glitch in contemporary culture are also contemplated (Hainge, Krapp, Bates, Sangild, Menkman, Briz, among others)